MIcrostrip disk resonators for filters fabricated from tbcco thin films - Jenkins, A; Kale, K; Edwards, D; Dew-Hughes, D (1997)
Microstrip disk type resonators have been designed and tested. These have been fabricated from TBCCO2212 thin films deposited by DC sputtering onto2cm square LaAlO3 substrates. The R of such large area films has been measured at 40 GHz using a copper end wall replacement cavity and shown to be less than 200uQ scaled to 10 GHz and at 80K. Q values of 2 to 6 GHz disk resonators have demonstrated considerable improvements when compared to both linear HTS microstrip resonators and comparable copper disk resonators. Additionally preliminary results for the performance of such disk resonators as a function of microwave power will be presented for application in high power filters. ©1997 IEEE.